The Role of Post-Translational Modifications on the Structure and Function of Tau Protein - Ye, Haiqiong; Han, Yue; Li, Ping; Su, Zhengding; Huang, Yongqi (Journal of molecular neuroscience, 2022)
Involving addition of chemical groups or protein units to specific residues of the target protein, post-translational modifications (PTMs) alter the charge, hydrophobicity, and conformation of a protein, which in tune influences protein function, protein − protein interaction, and protein aggregation. While the occurrence of PTMs is dynamic and subject to regulations, conformational disorder of the target protein facilitates PTMs. The microtubule-associated protein tau is a typical intrinsically disordered protein that undergoes a variety of PTMs including phosphorylation, acetylation, ubiquitination, methylation, and oxidation. Accumulated evidence shows that these PTMs play a critical role in regulating tau-microtubule interaction, tau localization, tau degradation and aggregation, and reinforces the correlation between tau PTMs and pathogenesis of neurodegenerative disease. Here, we review tau PTMs with an emphasis on their influence on tau structure. With available biophysical characterization results, we describe how PTMs induce conformational changes in tau monomer and regulate tau aggregation. Compared to functional analysis of tau PTMs, biophysical characterization of tau PTMs is lagging. While it is challenging, characterizing the specific effects of PTMs on tau conformation and interaction is indispensable to unravel the tau PTM code.